Realising embedded stiffness in hydraulic implementations of stiffness-damping-inertance configurations. (November 2022) - Zhang, Sara Y; Yuan, Hui; Jiang, Jason Z; Neild, Simon; Ren, Wei-Xin
The performance benefits of passive vibration suppression with network configurations consisting of stiffness, damping and inertance elements have been demonstrated for a wide range of mechanical systems. Considering physical implementations of these beneficial network configurations, hydraulic realisations have the advantages of durability and simplicity for integration with existing hydraulic dampers. Such designs are exemplified by fluid inerters and fluid-inerter-damper devices. However, in contrast to the convenience of realising inertance and damping elements, realising 'embedded' stiffness is very challenging. We use 'embedded' to refer to a network element, which is not purely in series or in parallel with the remainder of the network but instead lies within the network layout. In this work, a setup using a rubber membrane to realise such embedded stiffness is proposed, together with a procedure for hydraulic implementations of any stiffness-damping-inertance configurations. The nonlinear properties of the embedded stiffness due to rubber membrane properties are then investigated both theoretically and experimentally. In addition, the effectiveness of both the membrane setup and the design procedure are demonstrated via a case study of suspension design for passenger vehicle ride comfort enhancement.